Emotion recognition of students during e-learning through online conference meeting - Panichkriangkrai, Chulapong; Silapasuphakornwong, Piyarat; Saenphon, Thirachit (Science, Engineering and Health Studies, 2021)
Due to the outbreak of COVID-19, online learning has become a way of life. The objective of this study was to propose techniques to detect students’ emotions while studying via online video conferencing. This proposed technique, which updates the facial emotion image of the current class-member, enables the system to achieve a highly accurate performance for facial emotion recognition. This proposed technique can be applied to online teaching systems. As a result, instructors can identify the interest levels of each learner using the interest assessment system, which measures and monitors the period of tiresomeness of each learner. The results showed that our techniques achieved a high percentage of accuracy for each emotion, that is, sleepy/bored = 93.3%, confused = 94.3%, neutral = 92.6%, and happy = 97.2%, which was higher than the convolutional neural network-based emotion recognition system. The proposed system was applied to a real class and satisfactory overall results of 88.7% were achieved. This study proved the feasibility of the proposed technique.